Correction to "When Ethical Leader Behavior Breaks Bad: How Ethical Leader Behavior Can Turn Abusive via Ego Depletion and Moral Licensing" by Lin et al. (2016). (Journal of Applied Psychology, 2026)
The article focuses on correcting several inaccurately reported root-mean-square error of approximation (RMSEA) values in a study examining how ethical leader behavior can become abusive through ego depletion and moral licensing. The corrected RMSEA values, all higher than originally reported, pertain to various models analyzed in two studies, including single-factor, five-factor measurement, and hypothesized path models. Despite these adjustments, the authors confirm that the overall conclusions of the research remain unchanged. The corrections were approved by two of the original authors, while the original data are no longer accessible for verification.